Plastic waste into reusable bricks for green building and landscaping materials - Sukairi, Muhammad Shahirul Afiq; Imran, Mohamad Farid; Muhammad Fadzli, Nik Muhammad Faiq 'Afif; Ghazni, Muhammad Abdul Aziz; Ahmad Fauzi, Najwa Rawaida (Pusat Asasi, UiTM Cawangan Dengkil, 2020)
Today's world is seeing an increase in waste that is causing damage to the earth. The earth is exposed to the extremely polluted environment if the waste is not properly managed. The main objective of this innovation is to reduce the current plastic waste that is rising rapidly throughout the years while producing a material that can be use in the landscaping and construction industry. This work uses Polypropylene (PP) which is a type of thermoplastic that can easily be found in plastic waste. It can be re-moulded and recyclable to create other materials which in this case a prototype plastic brick. The plastic brick was processed to mix with other materials as fillers. These include waste rubber powder, and calcium carbonate (CaCO3). From previous research papers and articles, it is found that these fillers can significantly improve the properties of polypropylene (PP). In this study, coconut ash was added to strengthen the bricks. Therefore, it is concluded that, these plastic bricks have the potential to meet market needs to replace standard clay bricks. To support the government's call for recycling of waste, this innovation has the potential to help reduce plastic waste, resulting in a product that can be categorized as a green technology product.